OBJEKTIFIKASI PEREMPUAN DALAM BERITA ONLINE (ANALISIS WACANA KRITIS PERSPEKTIF SARA MILLS) - Laeli, Indah Nur (LPPM-PMP Universitas Tidar, 2024)
This research analyses the coverage of gender violence in cyber media using Sara Mills' Critical Discourse Analysis approach. The focus of this research is to understand how language in the news can reflect and reinforce gender inequality, and how women are often objectified in news narratives. This study uses qualitative methods with content analysis and discourse analysis to explore the narrative, framing, and representation of gender violence in cyber media. Data sources were taken from online news published by iNews.com and Okezone.com, with examples of cases of objectification of women in the news. The results showed that the news often contains objectification of women, both in the context of rape and in coverage of female public figures, such as athletes. News coverage tends to use language and framing that reinforces negative gender stereotypes and turns women into sexual objects. Sara Mills' approach helps identify the position of subjects and objects in discourse, revealing the dynamics of power and ideology contained in news texts. This research contributes to understanding the role of the media in reproducing gender inequality and the importance of journalistic ethics in covering gender violence issues.